Let H(x)=4f(x) + 5g(x), where the graphs of f and g are shown in the figure. Find H`(1).

### Want to see the full answer?

Check out a sample Q&A here*arrow_forward*Check out a sample Q&A here

*star_border*

## Related Calculus Q&A

Find answers to questions asked by students like you.

Q: 5. Obtain the particular solution. y'"-2 y'+2 y=3e" cos 2x; when x 0, y=2,y'=3

A: Click to see the answer

Q: (x%ex - 2) Cln /x+il) edy xy =0 y CO) = -4 y'Co) =5 %3D

A: In this question, we find the largest interval for the solution existence of the differential…

Q: X - X (x -x* Y (r-F)} (x-X{r-F) Y-F 2 4 3 6. 6. Compute: X = Y = E(X-XXY-Y)- N-1 B A = Y - B*X = 2.…

A: The table is given as follows x (x-xbar) (x-xbar)^2 y (y-ybar) (y-ybar)^2 (x-xbar)*(y-ybar) 0…

Q: 8. Find the general solution of (x2 + y2 + 1) dx + (x2 – 2xy) dy = А. х2 - у? - ху — 1%3D Сх В. х2 +…

A: Click to see the answer

Q: -За + 2т — 11 se z < 0 ax + 2a – 2x² – x + 10 f(x) = se 0 < x < 1 x2 – x – 2 e2z–1 – r + 4, se 1< a

A: Function is continuous if right hand limit and left hand limit exists and equal.

Q: 3. Determine the general solution. a) y"–2y' – 3y= e* b) y"+9y= cos x

A: Click to see the answer

Q: 6. Find the general solution of (x + 2y - 1) dx + (x +2y +5) dy = 0 х +у - 6 In(7 -х - 2у) 3 x - y +…

A: Click to see the answer

Q: 3 9 dx dt -1 -3 with x(0) 4 Give your solution in real form. X1 = X2 = ||

A: Click to see the answer

Q: 3 9 dx dt -1 -3 with x(0) : 4 Give your solution in real form. X1 = X2 = 2. II

A: The objective is to solve the differential equation:

*question_answer*

Q: I (1-x) y"- 4x y'+ 5x = cos x. 2 * + tx° = 0 4. x + y = 0 5. x y' - 4 sen y = x² 6. y" - 6y"+ 3y"+…

A: As per our guidelines, I can answer only one question and maximum three subparts of a question.…

*question_answer*

Q: Find the general solution of y(4)+y'' = 3t2+4sin t-2 co

A: Click to see the answer

*question_answer*

Q: 4 Give the general solution to x²y' + xy = -2 cos(2x) y¯2

A: The solution is given as

*question_answer*

Q: -2 27. The first derivative of y = is (4x+1)3 а. -24 b. 24 C. -6 d. (4x + 1)* (4x + 1)* (4x + 1)*…

A: Click to see the answer

*question_answer*

Q: 4 y 2 4 10 12 -2- -4 -6 2 (a) dx Number 4 (b) f (x) dæ Number (c) f (x) da Number %3D -co

A: Since you have asked multiple questions, we will solve the first question for you. If you want any…

*question_answer*

Q: z.e +4 a'z cos(2x+y) z.e Solve ax 4 əx-əy axəy

A: Click to see the answer

*question_answer*

Q: 3 5. [20 points] Solve (x + y)dx+ dy=0 +x-

A: Click to see the answer

*question_answer*

Q: 0.2 X = -2 0.1 X = -1 0.1 X = 0 Px(x) = {0 X = 1 and X = 2 0.3 X = 3 0.3 Х—4 Y = |X|+1 if E[Y] =? ve…

A: Click to see the answer

*question_answer*

Q: 3X 7- (0²1)y=K²" yp-e (4X-3} 8-(0-20+4)y=x+3x-5x+2 yp=Dx yo= 3.2 -2K 2. to-(D²+2}y=x²+xre+cos3X éte…

A: Click to see the answer

*question_answer*

Q: 3. f(x) = -x² +1 Ex)(+x). x2 + x - 6 %3D Holes: Vert. Asy: Hor. Asy:

A: Now plotting the graph of given function we get :

*question_answer*

Q: 6. Find the general solution of (x+ 2y- 1) dx + (x + 2y + 5) dy = 0 x - y + 6 In(7 - x - 2y) x + y -…

A: Click to see the answer

*question_answer*

Q: 3 9-r22 1 dy dz dr 9-r2 0_æ²_22 (x² + y² + z²)1/2

A: Click to see the answer

*question_answer*

Q: 4.1+ ež - ) ež + (ež )y' = 0 ex + (ex )y' = 0

A: Click to see the answer

*question_answer*

Q: 2.x. 1. 2x -y²= 10 1 2. 2 y=1 3. e y=s | 4.5inTTX -y = 0 5. x -y=-1

A: Click to see the answer

*question_answer*

Q: 1, 0 2

A: Click to see the answer

*question_answer*

Q: How do you find the derviatives of each without simplifying? -using differentiating rules for…

A: Click to see the answer

*question_answer*

Q: V1-x2 3. Evaluate S S /1-x²-y² dxdydz V1-x2-y2-z2

A: We will solve the following.

*question_answer*

Q: 2. Obtain the particular solution. y"-y'-6y=0; when x=0, y=2,y'=1

A: Click to see the answer

*question_answer*

Q: (2n Yn+2 + ) yn+1 ) Yn = (2n + 5)2" cos (") %3D 2n+3 2n+

A: Click to see the answer

*question_answer*

Q: Show that y = - In x + 3x - 5 is a solution of y" -=0. Use y = - Inx+3x – 5 to find y' and y". y' =O

A: Click to see the answer

*question_answer*

Q: 2. Find the general solution. y' + sec x y = cos x. а. b. y' +y =÷(e* -e-*).

A: Click to see the answer

*question_answer*

Q: 6. Find the general solution of (x + 2y – 1) dx + (x + 2y + 5) dy = 0 x - y + 6 In(7 - x - 2y) x + y…

A: Answer is option D)

*question_answer*

Q: The solution of * x² +3y² dy/dx= 2ху In y=In (1+y^2/x^2)+C none of each other O x= (1+y^2/x^2)+C In…

A: Click to see the answer

*question_answer*

Q: 3. Obtain the Particular Solution when x = 4 and y = 1 (x+ y - 4)dx – (3x- y – 4)dy = 0

A: Click to see the answer

*question_answer*

Q: 6. y = xe* 7. y= 3x.e* 8. y = x² In(x) 9. y =x*(5x – 1) 10. y = (x² + 2x)5(3x-3 +x²)-7 11. y = (1 –…

A: Use product rule of differentiation.

*question_answer*

Q: sketch the region of integration, reverse the order of integration, and evaluate the integral.

A: To evaluate ∫02∫04-x2xe2y4-ydydx

*question_answer*

Q: 11. 11. The particular solution is A. f(x) = v2 cos x + 3 B. f(x) = V3– 2 cos x C. f(x) = - ecosx D.…

A: Answer

*question_answer*

Q: 6. Find the general solution of (cos y + ycos x) dx + (sin x - x sin y) dy = 0 A. x cos y + y sin x…

A: Click to see the answer

*question_answer*

Q: dy = -8xy² dx 3. Solve + 4x(4x+1) y-(8.x² +4x² -1) by knowing u =x is a solution.

A: Given: dydx=-8xy2+4x4x+1y-8x3+4x2-1

*question_answer*

Q: 3.Eliminate the arbitrary constant on the given equation: xsiny – x²y-3 = C

A: In this question we have to eliminate the arbitrary constant on the given equation.

*question_answer*

Q: 3.Eliminate the arbitrary constant on the given equation: xsiny – x²y-3 = C

A: Since you have posted multiple questions i can do first question as per our company guidelines…

*question_answer*

Q: 14 (3 3 1f y=/xL5x²–36 x15x²-36 X23x²+¥x-12 show that dy dx4 24

A: Click to see the answer

*question_answer*

Q: 3. Obtain the general solution of: (x – y)(4x + y) dx + x(5x – y) dy = 0

A: Click to see the answer

*question_answer*

Q: 4. (a) dzy Solve: dx2 + ( = 0. (b) Solve xy" + (1 – x)y' – 2(1+x)y = e-*(1 – 6x) by the method based…

A: We have, d2ydx2+dydx+dydx3=0 ..i Put dydx=v ⇒d2ydx2=dvdx Now substitute in equation i we get…

*question_answer*

Q: Use Gauss-Jordan elimination to find the complete solution of the system, or show that no solution…

A: The given system is: x+y-z-w=2x-y+z-w=02x +2w=22x+4y-4z-2w=6 The augmented matrix is:…

*question_answer*

Q: Q.No.3: a) Solve Cauchy-Euler equation d'y 3x3 dx3 d²y dx2 dy + 9x? + 6х— — бу %3 1+x3 dx

A: Click to see the answer

*question_answer*

Q: x' = (C )x ´sec X + 0, 1

A: Click to see the answer

*question_answer*

Q: (a) x² + zsen xyz = 0

A: Click to see the answer

*question_answer*

Q: x+x-2 dx If S (x²–1)(2x-x²) dx can be resolved into A S+ Bƒ f(x)dx + D ƒ g(x)dx , then

A: Using partial fraction to solve the problem.

*question_answer*

Q: 1. (16x y² etxy + y sec² (xy) – 2x + 3y) + (16x² y e*xy + x sec²(xy) + 3x)y' = 5

A: Given: 16xy2e4xy+y sec2xy-2x+3y+16x2ye4x+xsec2xy+3xy'=5

*question_answer*

Q: |1 X x21 |1 X YZ| 1 Y XZ = 1 Y Y2 1 Z XY Z 72

A: Click to see the answer